The Role of NLRP3 Inflammasome Activation Pathway of Hepatic Macrophages in Liver Ischemia–Reperfusion Injury - Wu, Tong; Zhang, Cheng; Shao, Tianfeng; Chen, Jianzhong; Chen, Diyu (Frontiers in Immunology, 2022)
Ischemia-reperfusion injury (IRI) is considered an inherent component involved in liver transplantation, which induce early organ dysfunction and failure. And the accumulating evidences indicate that the activation of host innate immune system, especially hepatic macrophages, play a pivotal role in the progression of LIRI. Inflammasomes is a kind of intracellular multimolecular complexes that actively participate in the innate immune responses and proinflammatory signaling pathways. Among them, NLRP3 inflammasome is the best characterized and correspond to regulate caspase-1 activation and the secretion of proinflammatory cytokines in response to various pathogen-derived as well as danger-associated signals. Additionally, NLRP3 is highly expressed in hepatic macrophages, and the assembly of NLRP3 inflammasome could lead to LIRI, which makes it a promising therapeutic target. However, detailed mechanisms about NLRP3 inflammasome involving in the hepatic macrophages-related LIRI is rarely summarized.Liver ischemia reperfusion injury (LIRI) is ic process that involves the local ischemic insult and sterile inflammatory response, which could induce early organ dysfunction and failure after liver transplantation. Accumulating evidence indicate that the activation of host innate immune system, especially Hhepatic macrophages mediated innate immune response , play a pivotal role in the progression of LIRI. Recent studies indicated activation of NLRP3 Inflammasomes in hepatic macrophages which result in is a kind of intracellular multimolecular complexes that actively participate in the innate immune responses and proinflammatory signaling pathways. Among them, NLRP3 inflammasome is the best characterized and is critical to regulate caspase-1 activation and the production secretion of proinflammatory cytokines IL-1β/IL-18 in response to various pathogen-derived as well as danger-associated stimulisignals. Additionally, NLRP3 is highly expressed in hepatic macrophages, and the assembly of NLRP3 inflammasome could leading to LIRI. Inhibition NLRP3 inflammasome , which makes itis a promising therapeutic target for LIRI. However, detailed mechanisms about NLRP3 inflammasome involving in the hepatic macrophages -related LIRI is rarely summarized. Here, we review and discuss the potential role of the NLRP3 inflammasome pathway of hepatic macrophages in LIRI, with highlights on currently available therapeutic options.